2019
DOI: 10.1126/science.aay9698
|View full text |Cite
|
Sign up to set email alerts
|

Constructive molecular configurations for surface-defect passivation of perovskite photovoltaics

Abstract: Surface trap–mediated nonradiative charge recombination is a major limit to achieving high-efficiency metal-halide perovskite photovoltaics. The ionic character of perovskite lattice has enabled molecular defect passivation approaches through interaction between functional groups and defects. However, a lack of in-depth understanding of how the molecular configuration influences the passivation effectiveness is a challenge to rational molecule design. Here, the chemical environment of a functional group that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
890
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,034 publications
(910 citation statements)
references
References 39 publications
17
890
0
3
Order By: Relevance
“…Intrinsically, A‐site cations contribute to thermal, light exposure, moisture, and mechanical stabilities, while mixed halides are found to produce more reproducible and thermally stable films with higher crystal qualities. [ 2–5 ] The MLMP Cs 0.05 MA 0.15 FA 0.8 Pb(I 0.83 Br 0.17 ) 3 with an amazing high PCE over 20% and an improved stability was first reported in 2016. [ 6,7 ] Recently, Amassian et al revealed their crystallization behaviors using an in situ time‐resolved grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsically, A‐site cations contribute to thermal, light exposure, moisture, and mechanical stabilities, while mixed halides are found to produce more reproducible and thermally stable films with higher crystal qualities. [ 2–5 ] The MLMP Cs 0.05 MA 0.15 FA 0.8 Pb(I 0.83 Br 0.17 ) 3 with an amazing high PCE over 20% and an improved stability was first reported in 2016. [ 6,7 ] Recently, Amassian et al revealed their crystallization behaviors using an in situ time‐resolved grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of functional molecules including Lewis acid and base, alkylammonium halide, and wide bandgap and hydrophobic polymers can passivate perovskite surface acting as interfacial modification layers. [ 2,18–27 ] However, it is still difficult to accurately identify defect types including Pb 2+ /halide vacancies, interstitial Pb 2+ /halides, and undercoordinated Pb 2+ /halides for these multicomponent perovskites. [ 11,28–30 ] Therefore, identifying defect types and adopting suitable passivators are crucial not only to boost the efficiency but also to slow down the moisture degradation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, x log P or partition coefficient (an indicator for hydrophobicity), complexity, and the number of carbons, iodines, or bromines generally have lower ranks in the model. If we consider the recently published capping layer materials, such as theophylline, caffeine, and theobromine, 15,16 assuming they were fabricated in the same manner as the materials in this study, the onsets are predicted to happen at 98, 309, and 105 minutes respectively. As a reference, PTEAI onset happens at (460 ± 110) minutes.…”
Section: Machine Learning Regression Feature Importance Ranking Andmentioning
confidence: 99%
“…Due to its lower number of hydrogen-bond donor and smaller polar surface area, caffeine is predicted to be more stable among these 3 materials, even though its surface passivation property is worse than theophylline. 15…”
Section: Machine Learning Regression Feature Importance Ranking Andmentioning
confidence: 99%
See 1 more Smart Citation